Continuum-based modeling large-strain plastic deformation of semi-crystalline polyethylene systems: Implication of texturing and amorphicity. (November 2021) - Yan, Zhu; Guo, Qiang; Zaïri, Fahmi; Zaoui, Ali; Jiang, Qifeng; Liu, Xiaobing
Abstract: The present contribution examines the ability of a constitutive model to capture polyethylene response variation with crystallinity. The model considers the elastic-viscoplastic crystal deformation and anisotropy due to the crystallographic texturing along with the amorphous chains network elastic-viscoplastic-viscohyperelastic deformation. The coupling between the two phases is performed by means of a multi-scale homogenization-based approach in which the interfacial interaction is considered. The model is applied on semi-crystalline polyethylene systems containing a broad range of crystallinities. Both monotonic and oligo-cyclic tensile loading sequences are considered upon large-strain plastic deformation. The model is found able to correctly capture the gradual transition of the rate-dependent monotonic response from a thermoplastic-like behavior at high crystallinity to a nearly elastomeric-like behavior at low crystallinity. The model abilities to capture cyclically loaded polyethylene systems are critically discussed. The influential and decisive role of the amorphous chains network alignment/relaxation on the cyclic stretching is emphasized by analyzing local stresses and stretches. Highlights: Polyethylene monotonic and oligo-cyclic tensile response variation with crystallinity. Multi-scale homogenization within elastic-viscoplastic-viscohyperelastic framework. Role of crystallographic texturing and amorphous chains network alignment/relaxation. Local stresses and stretches upon oligo-cyclic tensile loading sequences.